O ESPAÇO NAS POLÍTICAS PÚBLICAS:o caso da preservação e revitalização da Praia Grande em São Luís - COSTA, Sarany Rodrigues da (2017)
The space in public policies in São Luis. It analyzes the public policies directed to the Praia Grande, in the period from 1980 to 1993, and its relationship with the dynamics of space, in order to identify the contributions of these policies on the construction of an identity for St.Louis. To do this, it is a documentary research that uses corpus of type file, this being understood from the perspective of Foucault (2008), which considers the file as the law of what can be said about a given topic, the general system of formation and transformation. In this way, the file found in this study is composed mainly b y the set of documents that form the Program of Preservation and Revitalization of the Historic Center of São Luis (PPRCHSL), which is studied based on the Analysis of the Discourse (AD) of the French line, guided by the writings of philosopher Pêcheux (1995). The search starts with the discussion of the concept of space, and categories such as landscape and place, in the perspective of authors such as Santos (2012; 2014), Tuan (2013), Soja (1993). Subsequently it is made the characterization of the research object, the Praia Grande, which narrates the process of formation of urban space and highlights the work carried out on it. Below is the process of formation of the file on the preservation of cultural heritage in St. Louis and a discussion about the cultural studies and identity in breadth with the AD. To support the discussions about identity, it seeks to aid in cultural studies and its representatives: Hall (2011), Woodward (2000), Silva (2000; 1996). In another moment are presented the results of the analysis of the documents tributaries of the PPRCHSL, pointing to the existence of conceptions of social space, economic and social development, besides the presence of elements of the concepts of landscape, place and environmental heritage urban, showing thus the identities that emerge from the discourses present in that program, which, in turn, reflect the conceptions of space within it. Finally, you are presented with the final considerati ons obtained with the development of the work, which lead to the observation of effects of senses that point to the perception, in PPRCH, space with its social, economic and cultural life, beyond that which is able to make “relive” times and past experiences.